BUNGA ANGGREK DALAM HIASAN DINDING DENGAN TEKNIK BORDIR, SULAM DAN JAHIT APLIKASI PERCA - Cori Muharsi Wulandari, Drs. Erwin, M.Sn. (Universitas Negeri Padang, 2019)
The author's interest in orchids starts with a sense of admiration for their beautiful and elegant flower shapes. However, the authors chose the embroidery technique on the part (background), embroidery on orchids, and patchwork sewing applications on the leaves, because this technique is more interesting to the author's attention. But the main reason is that this technique has never been used by Fine Arts Students in their work. The work produced is titled gentleness, respect, freedom, grandeur, complement, bloom together and prosperity. The orchid is a beautiful flower and is most often used as an ornamental plant at home. Orchids also include types of flowers that have many variants, and their types are scattered throughout the tropics. Orchid flowers can be found growing in forests, in rocks, on land, and growing attached to trees.Keywords: Orchid flowers, embroidery, embroidery and sewing patchwork applications